Progress in glass sponge phylogenetics: a comment on Kersken et al. (2018) - Dohrmann, M. (Hydrobiologia, 2019)
Kersken et al. (Hydrobiologia 811:283–293, 2018) recently reported a phylogenetic analysis of ribosomal DNA of glass sponges (Porifera: Hexactinellida) including new specimens from the NE Pacific. Their study is important as it significantly increased the taxon sampling of this important deep-sea group. Unfortunately, there are several issues with these authors’ dataset assembly and choice of phylogenetic analysis methods. Furthermore, they did not consider previous literature that is highly relevant to interpretation of their results. Here I provide critically constructive comments on their paper and present an alternative analysis that utilizes established methodological techniques. I show that several of Kersken et al.’s findings and claims are unsustainable, and provide an extended discussion of the updated glass sponge phylogeny.